Electrodeposition of Silver Nanoparticles on Reduced Graphene Functionalized by Pyridine‐Pyridazine Units: Application to Surface‐Enhanced Raman Spectroscopy and Electrocatalysis. Issue 4 (25th January 2019) - Rus, Yahdi Bin; Galmiche, Laurent; Audebert, Pierre; Courty, Alexa; Maisonhaute, Emmanuel; Miomandre, Fabien
Abstract: A new and versatile method to prepare Ag nanoparticles on functionalized graphene sheets is described. In a first step, pyridine‐pyridazine units are introduced on graphene sheets by cycloaddition reaction with a tetrazine derivative. Then the material is coated on an electrode and electrodeposition is carried out to generate silver nanoparticles in a one‐step electroreduction process. The applied potential signal is shown to influence the size and dispersity of the particles in the composite. While larger particles are active in improving sensitivity of Surface‐Enhanced Raman Spectroscopy, smaller ones can be efficiently used in electrocatalysis, like for oxygen reduction. Both effects are demonstrated to highlight the versatility of the applications of these easily prepared nanocomposites. Abstract : Silver nanoparticles decorated graphene sheets are synthesized in a simple two‐step process : first pyridine‐pyridazine are introduced at the graphene surface by inverse Diels‐Alder reaction. Then electroreduction in presence of silver nitrate leads to nanoparticles. Application to SERS and electrocatalysis according to nanoparticle size are demonstrated.